Autoestima y consumo de alcohol como predictores de la satisfacción con la vida en jóvenes de la ciudad de Juliaca - Benavente Pacori, Abel (2023)
Objective: to determine if self-esteem and alcohol consumption are predictors of life satisfaction      in young people from the city of Juliaca. The specific objectives are; determine if self-esteem is a predictor of life satisfaction and determine if alcohol consumption is a predictor of life satisfaction. Methodology: non-experimental cross-sectional design and quantitative approach. The population is made up of 30,135 people of both sexes between 19 and 24 years of age from the city of Juliaca. The sample consisted of 380 subjects, calculated from probabilistic sampling due to the high number of subjects. The instruments used for the research were the COOPERSMITH Self-Esteem Questionnaire (Adults), the Alcohol Use Disorders Identification Test (AUDIT) and the Life Satisfaction Scale. Results: a coeffcient of relationship R=0.608 is observed with a level of significance p=0.000, in addition, an adjusted coeffcient of determination R2=0.366 is observed. Conclusion: life satisfaction can be predicted by up to 36%. Self-esteem is a directly predictive variable of moderate intensity      of satisfaction with life. And the variable alcohol consumption is considered an indirectly predictive variable of low intensity for satisfaction with life.